The role of Malaysia in the United Nations Security Council - Wah, Yee Jing; Abdul Wahab Jumrah (Fakulti Undang-undang, Universiti Kebangsaan Malaysia, 2017)
During the 69th session of United Nations General Assembly, Malaysia has once again been elected as non-permanent member of the United Nations Security Council (hereinafter refer as “UNSC”) for two-year mandate commencing on 1st of January 2015.1 This article discusses the role and nature of Malaysia’s foreign policy in serving the non-permanent seat of the UNSC. In Part I, the article discusses the key roles of non-permanent members in the UNSC and the importance of UNSC as part of the organization. In Part II, the article broadly discusses the foreign policy of Malaysia propounded nationally in maintaining the relationship between regional and international organizations as well as multilateral relationships with other states. In Part III, the article will provide examples on the application of national foreign policy under the UNSC when deliberating peace and security issues under the mandate as UNSC’s non-permanent member.